The Effect of Reputation on Selling Prices in Auctions - Oliver Gürtler; Christian Grund (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In economic approaches it is often argued that reputation considerations influence the behavior of individuals or firms and that reputation influences the outcome of markets. Empirical evidence is rare though. In this contribution we argue that a positive reputation of sellers should have an effect on selling prices. Analyzing auctions of popular DVDs at eBay we, indeed, find support for this hypothesis. Secondary, we unmask the myth that it is promising for eBay sellers to let their auction end at the evening, when many potential buyers may be online.
urn:nbn:de:bvb:19-epub-13437-6
Keywords: D44; D82; K12; L81; 330; Reputation; eBay feedback system; auction